Evaluación técnico-económica de sistemas de refrigeración para la industria plástica en la producción de preforma (2021)
For the production of preform in the plastic industry injection machines are used, in the case of study the Husky machinery is taken as a reference, which needs a cooling system for both its hydraulic system and the mold in which the preform is produced; Having said this, the project is evaluated with a bibliographic search for alternatives such as refrigeration systems, and then by means of a decision matrix, make the comparison of the alternatives found through technical-environmental criteria in order to obtain the best bibliographic alternative, later With the use of software, model said alternative, thus estimating the behavior it will have for the operating conditions of the Husky machinery, finally the development of economic viability by means of a financial indicator in order to evaluate if the alternative is profitable both technically as financially.